Aortic atresia with complete transposition. Issue 5 (May 1987) - Lo, R N; Lau, K C; Aung-Khin, M
Abstract : Aortic atresia with ventriculoarterial discordance in a three day old neonate was studied by cross sectional echocardiography and the anatomy was confirmed at necropsy.